What's biology all about? - Maskell, Hazel; Larkum, Adam Dickins, Rosie Chisholm, Jane (Usborne London, 2012)
Explaining biology in an informal, fun and informative way, this title offers children an approachable source of information on key subjects such as the life cycle, the human body, plantlife, evolution and ecosystems. It is filled with information from the headlines on such topical issues as stem cell research and dinosaur discoveries.